Gender in Socio-Legal Teaching and Research in Germany. Issue 7 (October 2020) - Schultz, Ulrike
Abstract: Gender in socio-legal teaching and research in Germany is a story of impediments, hindrances, and of singleperson initiatives—my personal history being a part of this. But it is also a story of influences upon the impulse and inspiration to undertake socio-legal work. My Article is therefore influenced by (feminist) standpoint theory (Harding 1991). Germany has had a very conservative family culture and, over the past decades, many of the legal regulations that infringed upon women have had to be adapted, in what was quite a tedious political process, to comply with the German Constitution's gender equality clause. Only in the past decade has gender awareness in law faculties increased and gained acceptance, usually as a result of greater focus on diversity issues, and anti-discrimination legislation. Obstacles have resulted from a lack of cooperation between the actors in social sciences and law, as well as in academia and gender equality practice, and a lack of understanding between more conservative and more progressive women. Socio-legal research was, and is, needed to deliver empirical evidence and provide theoretical foundations for cultural and legal changes as societies progress towards gender equality. Socio-legal teaching is needed to alert lawyers to necessary change, to enable them to undertake informed critique, and to prepare them to act. There are, however, marked deficits in socio-legal teaching and research on gender. In spite of an increased political acceptance, gender equality is still mainly a women's project.